Incidental diagnosis of primary papillary carcinoma arising from thyroglossal duct cyst: A rare case report - Rawte, Mukta; Majumder, Nabaneet; Dafle, Virendra; Purohit, Pramod (Asian Journal of Medical Sciences, 2014)
Thyroglossal duct cysts are most common congenital anomalies in thyroid development and are usually presented with midline neck swelling. The co-existence of carcinoma in thyroglossal duct cyst’s is extremely rare. We, herein present a case of primary papillary carcinoma arising from thyroglossal duct cyst in a 45 year old woman. DOI: http://dx.doi.org/10.3126/ajms.v6i1.9305 Asian Journal of Medical Sciences Vol.6(1) 2015 129-131